A kind of protective slag for eliminating the carbon-rich layer of crystallizer

By using a modified protectant in the protective slag, the problem of the high carbon content in the traditional protective slag is solved, and the effect of eliminating the carbon rich layer and improving the quality of the casting billet is achieved.

CN119140773BActive Publication Date: 2025-04-15LUOYANG KEFENG NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411621530.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-04-15
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

Traditional protective slag contains a high carbon content, resulting in a carbon-rich layer forming inside the crystallizer, affecting the quality of the casting billet.

Method used

Using a protective slag including calcium oxide, silicon oxide, calcium fluoride, aluminum oxide, magnesium oxide, zirconium oxide, flux and a modification protector, the modification protector is prepared by mixing metal chromium and metal cadmium and compounding with malonic acid to reduce the thickness of the carbon-rich layer by reducing the melting point of chromium and improving dispersion.

Benefits of technology

Effectively eliminate the carbon-rich layer of the crystallizer, improve the surface quality of the casting billet, and improve the lubricating effect and fluidity of the protective slag.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005229849310000111
    Figure GDA0005229849310000111
Patent Text Reader

Abstract

The invention relates to the technical field of protective slag preparation, and relates to a protective slag for eliminating a carbon-rich layer of a crystallizer. The protective slag comprises the following components in parts by weight: 38-44 parts by weight of calcium oxide, 53-67 parts by weight of silicon dioxide, 8-13 parts by weight of calcium fluoride, 5-7 parts by weight of aluminum oxide, 3-9 parts by weight of magnesium oxide, 1-5 parts by weight of zirconium oxide, 4-6 parts by weight of flux, and 1-3 parts by weight of a modified protective agent, wherein the modified protective agent is obtained by mixing metal chromium and metal cadmium in a mass ratio of 3:5-7, and then undergoing mixed modification treatment and then compounding with malonic acid. The modified protective agent is adopted, and the metal cadmium is used to react with the protective slag and carbon elements in molten steel to eliminate the generation of a carbon-rich layer on the crystallizer. The chromium is mixed and modified with the metal cadmium to reduce the melting point of the chromium, and the problem of incomplete melting of the chromium in the protective slag is avoided. The surface treatment with malonic acid is adopted to improve the dispersibility of the chromium in the protective slag, so that the protective slag can effectively eliminate the carbon-rich layer of the crystallizer and improve the surface quality of the ingot.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of protective slag preparation, in particular to a protective slag for eliminating a carbon-rich layer of a crystallizer. Background Art

[0002] A crystallizer is a device used to shape and initially solidify molten steel. It is a copper container, usually placed vertically or tilted. Its internal shape determines the cross-sectional shape of the final ingot (such as slabs, billets, etc.), and the inner wall of the crystallizer is usually very smooth to facilitate smooth demolding of the ingot. During the continuous casting process, high-temperature molten steel is poured into the crystallizer. Under the action of cooling water, the molten steel first begins to solidify in the crystallizer to form a solid shell. As the continuous casting machine draws the billet, the shell continues to grow until it is completely solidified into a billet. If the protective slag contains carbon or carbon compounds, it is easy to cause carbon increase in the molten steel, thereby forming a carbon-rich layer inside the crystallizer. This layer of sediment is called a "carbon-rich layer". The presence of the carbon-rich layer will lead to a decrease in the surface quality of the ingot, such as dents, cracks and other problems.

[0003] Traditional protective slag does play an important role in isolating air, reducing heat loss, and promoting uniform growth of the billet shell during the continuous casting process. However, its protective slag often contains a high carbon content, and it is difficult to avoid the formation of a carbon-rich layer, which in turn affects the quality of the cast billet. In view of this, a protective slag is provided for eliminating the carbon-rich layer in the crystallizer. Summary of the invention

[0004] The object of the present invention is to provide a protective slag for eliminating the carbon-rich layer of the crystallizer, so as to solve the problem of the formation of the carbon-rich layer of the crystallizer proposed in the above-mentioned background technology.

[0005] To achieve the above object, the present invention provides a protective slag for eliminating the carbon-rich layer of a crystallizer, comprising the following components in parts by weight: 38-44 parts by weight of calcium oxide, 53-67 parts by weight of silicon dioxide, 8-13 parts by weight of calcium fluoride, 5-7 parts by weight of aluminum oxide, 3-9 parts by weight of magnesium oxide, 1-5 parts by weight of zirconium oxide, 4-6 parts by weight of flux and 1-3 parts by weight of modified protective agent;

[0006] The modified protective agent is prepared by mixing metal chromium and metal cadmium in a mass ratio of 3:5-7, and then undergoing mixed modification treatment and then compounding with malonic acid.

[0007] As a further improvement of the technical solution, the specific preparation method of the modified protective agent is as follows:

[0008] In an atmosphere of inert gas argon, a mixture of chromium and cadmium is heated to 1900-2000° C. using a high-frequency induction furnace, and heating and stirring are continued to ensure that all metals are completely melted and evenly mixed, and the molten alloy is poured into a preheated mold, and allowed to cool naturally to obtain a chromium-cadmium alloy, malonic acid is added to deionized water and stirred to form a solution, and the pH value is adjusted with a sodium hydroxide solution, and then the chromium-cadmium alloy is immersed in the above solution to ensure that the surface of the alloy is completely covered, and immersed in a constant temperature water bath. After the reaction is completed, the alloy sample is taken out from the solution, and is thoroughly washed with deionized water to remove unreacted malonic acid or other impurities, and washed with anhydrous ethanol, and dried naturally to obtain a modified protective agent.

[0009] Since the protective slag contains carbon or carbon compounds, the carbon in the protective slag exists in the form of dissolved carbon or undissolved carbon particles. The dissolved carbon exists in the slag in atomic form and is transferred to the molten steel by diffusion; while the undissolved carbon particles float up due to buoyancy, or are deposited near the wall of the crystallizer as the slag flows. When the sinking speed of these carbon particles is greater than their floating speed, the carbon particles will directly contact the molten steel. Since the solubility of carbon in molten steel is relatively large, it is easy to cause carbon increase in the molten steel, thereby forming a carbon-rich layer inside the crystallizer. Metallic chromium can react with the carbon or carbon compounds in the protective slag and the carbon precipitated in the molten steel to form a relatively stable compound, which is not easy to further decompose back into carbon atoms, thereby reducing the diffusion rate of carbon from molten steel to slag, reducing the thickness of the carbon-rich layer, and improving the efficiency of continuous casting and the surface quality of the ingot. However, the melting point of metallic chromium is relatively high, which means that during the continuous casting process, chromium is added to the protective slag in the form of pure metal and will not be completely melted, especially when the temperature of the protective slag is lower than its melting point. It will be in the slag. The formation of solid particles increases the viscosity of the slag, resulting in a decrease in fluidity, which will affect the ability of the protective slag to cover the molten steel, and further affect the purity of the molten steel. At the same time, since an important function of the protective slag is to provide a good insulating layer between the crystallizer and the molten steel, the presence of solid chromium particles will change the thermal conductivity of the protective slag, resulting in an enhanced cooling effect of the crystallizer, which is not conducive to the uniform solidification of the molten steel in the crystallizer, and therefore the chromium needs to be modified; and the melting point of metallic cadmium is low, much lower than the continuous casting temperature of steel, so the purpose of lowering the melting point of the metal is achieved by mixing and modifying metallic chromium and metallic cadmium. The presence of metallic cadmium can lower the melting point of the protective slag, making the slag easier to flow and form a uniform liquid layer, thereby improving its lubrication effect, reducing the friction between the billet and the slag, and being beneficial to improving the surface quality of the ingot. At the same time, the carboxyl group on the malonic acid combines with the active site on the metal surface to form a coordination bond, which is adsorbed on the surface of the metal particles to form a protective film, providing a steric hindrance effect, preventing the agglomeration of the particles in the protective slag, and improving the dispersion of the particles in the protective slag.

[0010] As a further improvement of the technical solution, the mass fraction of the malonic acid is 12-18%.

[0011] As a further improvement of the technical solution, the molar concentration of the sodium hydroxide solution is 0.1-1 mol / L.

[0012] As a further improvement of the technical solution, the pH value is adjusted to 2-4.

[0013] As a further improvement of the technical solution, the temperature of the constant temperature water bath is set to 60-90° C., and the reaction time is 2-3 hours.

[0014] As a further improvement of the technical solution, the flux is one or more combinations of sodium oxide, potassium oxide and lithium oxide.

[0015] As a further improvement of the technical solution, the specific preparation method of the protective slag is as follows:

[0016] Put calcium oxide, silicon dioxide, calcium fluoride, aluminum oxide, magnesium oxide and zirconium oxide into a mixer and mix them preliminarily for 30-40 minutes, then add the modified protective agent, and continue mixing for 10-20 minutes to make the protective agent evenly distributed in each component, put the mixed material into an oven, dry it at 100-120°C for 1-2 hours, put the dried material into a muffle furnace for calcination, and the calcined material is naturally cooled to room temperature. The cooled protective slag is sieved through a sieve to remove large particles to obtain a protective slag that eliminates the carbon-rich layer of the crystallizer.

[0017] As a further improvement of the technical solution, the calcination temperature of the muffle furnace is 800-1000° C., and the calcination time is 1-2 hours.

[0018] As a further improvement of the technical solution, the particle size of the protective slag is 0.2-1 mm.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] In the protective slag for eliminating the carbon-rich layer of the crystallizer, a modified protective agent is used, and metal cadmium can react with the protective slag and the carbon element in the molten steel to generate a stable compound, thereby eliminating the generation of the carbon-rich layer on the crystallizer. The melting point of chromium is reduced by mixing and modifying with the metal cadmium, thereby avoiding the problem of incomplete melting of chromium in the protective slag. At the same time, malonic acid is used for surface treatment to improve its dispersibility in the protective slag and prevent particles from agglomerating in the protective slag, so that the prepared protective slag can not only effectively eliminate the carbon-rich layer of the crystallizer, but also improve the lubricating effect of the protective slag and improve the surface quality of the ingot. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0022] A protective slag for eliminating a carbon-rich layer in a crystallizer comprises the following components in parts by weight: 38-44 parts by weight of calcium oxide, 53-67 parts by weight of silicon dioxide, 8-13 parts by weight of calcium fluoride, 5-7 parts by weight of aluminum oxide, 3-9 parts by weight of magnesium oxide, 1-5 parts by weight of zirconium oxide, 4-6 parts by weight of flux and 1-3 parts by weight of a modified protective agent; wherein the modified protective agent is prepared by mixing metal chromium and metal cadmium in a mass ratio of 3:5-7, and then subjecting the mixed modified agent to a composite with malonic acid; the flux is one or more combinations of sodium oxide, potassium oxide and lithium oxide.

[0023] Among them, sodium oxide is preferably used as the flux.

[0024] Example 1: In this example, the specific preparation method of the protective slag for eliminating the carbon-rich layer of the crystallizer is as follows:

[0025] Prepare the following components: 38 parts by weight of calcium oxide, 53 parts by weight of silicon dioxide, 8 parts by weight of calcium fluoride, 5 parts by weight of aluminum oxide, 3 parts by weight of magnesium oxide, 1 part by weight of zirconium oxide, 4 parts by weight of sodium oxide flux and 3 parts by weight of modified protective agent; wherein the modified protective agent is obtained by mixing metal chromium and metal cadmium in a mass ratio of 3:5 and then compounding with malonic acid after mixed modification treatment, the mass fraction of malonic acid is 12%, and the molar concentration of the sodium hydroxide solution is 1 mol / L;

[0026] In an atmosphere of inert gas argon, a mixture of chromium and cadmium is heated to 1900°C using a high-frequency induction furnace, and heating and stirring are continued to ensure that all metals are completely melted and evenly mixed, and the molten alloy is poured into a preheated mold, and allowed to cool naturally to obtain a chromium-cadmium alloy, malonic acid is added to deionized water and stirred to form a solution, and the pH value is adjusted to 3 with a sodium hydroxide solution, and then the chromium-cadmium alloy is immersed in the above solution to ensure that the surface of the alloy is completely covered, and immersed in a constant temperature water bath, the temperature is set to 80°C, and the reaction time is 3h. After the reaction is completed, the alloy sample is taken out from the solution, and is thoroughly washed with deionized water to remove unreacted malonic acid or other impurities, and washed with anhydrous ethanol, and dried naturally to obtain a modified protective agent;

[0027] Calcium oxide, silicon dioxide, calcium fluoride, aluminum oxide, magnesium oxide and zirconium oxide are placed in a mixer and preliminarily mixed for 30 minutes. Then, a modified protective agent is added and mixing is continued for 20 minutes to make the protective agent evenly distributed in each component. The mixed material is placed in an oven and dried at 120°C for 2 hours. The dried material is placed in a muffle furnace and calcined at 1000°C for 2 hours. The calcined material is naturally cooled to room temperature. The cooled protective slag is sieved through a sieve to remove large particles to obtain a protective slag that eliminates the carbon-rich layer of the crystallizer.

[0028] Example 2: In this example, the specific preparation method of the protective slag for eliminating the carbon-rich layer of the crystallizer is as follows:

[0029] Prepare the following components: 38 parts by weight of calcium oxide, 53 parts by weight of silicon dioxide, 8 parts by weight of calcium fluoride, 5 parts by weight of aluminum oxide, 3 parts by weight of magnesium oxide, 1 part by weight of zirconium oxide, 4 parts by weight of sodium oxide flux and 3 parts by weight of modified protective agent; wherein the modified protective agent is obtained by mixing metal chromium and metal cadmium in a mass ratio of 3:6 and then compounding with malonic acid after mixed modification treatment, the mass fraction of malonic acid is 12%, and the molar concentration of the sodium hydroxide solution is 1 mol / L;

[0030] In an atmosphere of inert gas argon, a mixture of chromium and cadmium is heated to 1900°C using a high-frequency induction furnace, and heating and stirring are continued to ensure that all metals are completely melted and evenly mixed, and the molten alloy is poured into a preheated mold, and allowed to cool naturally to obtain a chromium-cadmium alloy, malonic acid is added to deionized water and stirred to form a solution, and the pH value is adjusted to 3 with a sodium hydroxide solution, and then the chromium-cadmium alloy is immersed in the above solution to ensure that the surface of the alloy is completely covered, and immersed in a constant temperature water bath, the temperature is set to 80°C, and the reaction time is 3h. After the reaction is completed, the alloy sample is taken out from the solution, and is thoroughly washed with deionized water to remove unreacted malonic acid or other impurities, and washed with anhydrous ethanol, and dried naturally to obtain a modified protective agent;

[0031] Calcium oxide, silicon dioxide, calcium fluoride, aluminum oxide, magnesium oxide and zirconium oxide are placed in a mixer and preliminarily mixed for 30 minutes. Then, a modified protective agent is added and mixing is continued for 20 minutes to make the protective agent evenly distributed in each component. The mixed material is placed in an oven and dried at 120°C for 2 hours. The dried material is placed in a muffle furnace and calcined at 1000°C for 2 hours. The calcined material is naturally cooled to room temperature. The cooled protective slag is sieved through a sieve to remove large particles to obtain a protective slag that eliminates the carbon-rich layer of the crystallizer.

[0032] Example 3: In this example, the specific preparation method of the protective slag for eliminating the carbon-rich layer of the crystallizer is as follows:

[0033] Prepare the following components: 38 parts by weight of calcium oxide, 53 parts by weight of silicon dioxide, 8 parts by weight of calcium fluoride, 5 parts by weight of aluminum oxide, 3 parts by weight of magnesium oxide, 1 part by weight of zirconium oxide, 4 parts by weight of sodium oxide flux and 3 parts by weight of modified protective agent; wherein the modified protective agent is obtained by mixing metal chromium and metal cadmium in a mass ratio of 3:7 and then compounding with malonic acid after mixed modification treatment, the mass fraction of malonic acid is 12%, and the molar concentration of sodium hydroxide solution is 1 mol / L;

[0034] In an atmosphere of inert gas argon, a mixture of chromium and cadmium is heated to 1900°C using a high-frequency induction furnace, and heating and stirring are continued to ensure that all metals are completely melted and evenly mixed, and the molten alloy is poured into a preheated mold, and allowed to cool naturally to obtain a chromium-cadmium alloy, malonic acid is added to deionized water and stirred to form a solution, and the pH value is adjusted to 3 with a sodium hydroxide solution, and then the chromium-cadmium alloy is immersed in the above solution to ensure that the surface of the alloy is completely covered, and immersed in a constant temperature water bath, the temperature is set to 80°C, and the reaction time is 3h. After the reaction is completed, the alloy sample is taken out from the solution, and is thoroughly washed with deionized water to remove unreacted malonic acid or other impurities, and washed with anhydrous ethanol, and dried naturally to obtain a modified protective agent;

[0035] Calcium oxide, silicon dioxide, calcium fluoride, aluminum oxide, magnesium oxide and zirconium oxide are placed in a mixer and preliminarily mixed for 30 minutes. Then, a modified protective agent is added and mixing is continued for 20 minutes to make the protective agent evenly distributed in each component. The mixed material is placed in an oven and dried at 120°C for 2 hours. The dried material is placed in a muffle furnace and calcined at 1000°C for 2 hours. The calcined material is naturally cooled to room temperature. The cooled protective slag is sieved through a sieve to remove large particles to obtain a protective slag that eliminates the carbon-rich layer of the crystallizer.

[0036] Example 4: In this example, the specific preparation method of the protective slag for eliminating the carbon-rich layer of the crystallizer is as follows:

[0037] Prepare the following components: 44 parts by weight of calcium oxide, 67 parts by weight of silicon dioxide, 13 parts by weight of calcium fluoride, 7 parts by weight of aluminum oxide, 9 parts by weight of magnesium oxide, 5 parts by weight of zirconium oxide, 6 parts by weight of sodium oxide flux and 3 parts by weight of modified protective agent; wherein the modified protective agent is obtained by mixing metal chromium and metal cadmium in a mass ratio of 3:6 and then compounding with malonic acid after mixed modification treatment, the mass fraction of malonic acid is 12%, and the molar concentration of the sodium hydroxide solution is 1 mol / L;

[0038] In an atmosphere of inert gas argon, a mixture of chromium and cadmium is heated to 1900°C using a high-frequency induction furnace, and heating and stirring are continued to ensure that all metals are completely melted and evenly mixed, and the molten alloy is poured into a preheated mold, and allowed to cool naturally to obtain a chromium-cadmium alloy, malonic acid is added to deionized water and stirred to form a solution, and the pH value is adjusted to 3 with a sodium hydroxide solution, and then the chromium-cadmium alloy is immersed in the above solution to ensure that the surface of the alloy is completely covered, and immersed in a constant temperature water bath, the temperature is set to 80°C, and the reaction time is 3h. After the reaction is completed, the alloy sample is taken out from the solution, and is thoroughly washed with deionized water to remove unreacted malonic acid or other impurities, and washed with anhydrous ethanol, and dried naturally to obtain a modified protective agent;

[0039] Calcium oxide, silicon dioxide, calcium fluoride, aluminum oxide, magnesium oxide and zirconium oxide are put into a mixer and preliminarily mixed for 30 minutes, then a modified protective agent is added and mixed for 20 minutes to make the protective agent evenly distributed in each component, the mixed material is put into an oven and dried at 120°C for 2 hours, the dried material is put into a muffle furnace and calcined at 1000°C for 2 hours, the calcined material is naturally cooled to room temperature, the cooled protective slag is screened through a sieve, and after removing large particles, a protective slag that eliminates the carbon-rich layer of the crystallizer is obtained.

[0040] Comparative Example 1: The method of Example 2 was adopted, and the amount of the modified protective agent added was 0.01 parts by weight.

[0041] Comparative Example 2: The method of Example 2 was adopted to prepare the modified protective agent without using malonic acid surface treatment.

[0042] Comparative Example 3: The method of Example 2 was adopted to directly add metallic chromium and metallic cadmium to the protective slag without performing a mixed modification treatment or a malonic acid surface treatment.

[0043] The present invention prepares a protective slag for eliminating the carbon-rich layer of the crystallizer. In the application of the protective slag preparation technology field, the protective slag has a good effect of eliminating the carbon-rich layer of the crystallizer. The specific detection is shown in the following table:

[0044] Through continuous casting simulation experiments, the effect of eliminating the carbon-rich layer of the crystallizer is characterized. The size of the crystallizer is 100mm×100mm×1000mm. Low carbon steel is selected as the standard molten steel. The typical composition is 0.05-0.15% C, and the rest is iron and a small amount of manganese, silicon, etc. The molten steel is heated to 1550-1600℃ using an electric arc furnace or an induction furnace to ensure that the molten steel is uniform and free of impurities. The heated molten steel is poured into the crystallizer, and attention is paid to keeping the molten steel level stable. The crystallizer is first preheated to 200℃, and a layer of protective slag is evenly covered on the surface of the molten steel with a thickness of about 20mm. The continuous casting machine is started, and the pulling speed is controlled between 0.5-1.5m / min to keep the pulling speed constant , ensure that the molten steel in the crystallizer flows smoothly, adjust the cooling water flow through the cooling water circulation system to ensure that the molten steel in the crystallizer is evenly cooled, cut samples 100mm×100mm from both ends and the middle of the continuous casting billet, use sandpaper or clean the sample surface to ensure that the surface is flat, free of oxide scale and impurities, use a portable ultrasonic thickness gauge and calibrate it, use water as an ultrasonic coupling agent, apply an appropriate amount of coupling agent on the sample surface, ensure good contact between the probe and the sample surface, place the ultrasonic probe steadily on the sample surface, apply moderate pressure to ensure good contact, read the thickness value on the thickness gauge, and record it, perform multiple measurements at different positions of the sample and take the average value.

[0045] The obtained data are shown in Table 1:

[0046] Table 1 Performance data of Examples 1-4 and Comparative Examples 1-3

[0047]

[0048] By comparing Examples 1-4 with Comparative Examples 1-3, it can be seen that in a protective slag for eliminating the carbon-rich layer of a crystallizer, the modified protective agent has a significant effect on the carbon-rich layer of the crystallizer.

[0049] According to Examples 1-3, it can be seen that as the proportion of components in the modified protective agent continues to change, the effect of eliminating the carbon-rich layer in the crystallizer continues to change. This is because chromium can react with carbon or carbon compounds in the protective slag to form relatively stable compounds. The addition of cadmium can lower the melting point of the alloy, making the alloy easier to melt in the protective slag. As the proportion of cadmium further increases, excess cadmium will undergo unnecessary side reactions with other components, or form unstable intermediates, thereby reducing the overall effect of eliminating the carbon-rich layer.

[0050] According to Example 2 and Example 4, as the contents of other components in the protective slag continue to change, the effect of eliminating the carbon-rich layer in the crystallizer has almost no obvious change. This is because the modified protective agent plays a leading role in the process of eliminating the carbon-rich layer. Even if the contents of other components in the protective slag change, as long as the addition amount and proportion of the modified protective agent remain stable, its effect will not change significantly.

[0051] According to the above test experiments, Example 2 is used as the optimal example and compared with Comparative Examples 1-2 respectively.

[0052] By comparing Example 2 with Comparative Example 1, it can be seen that the effect of eliminating the carbon-rich layer in the crystallizer is worse when the addition amount of the modified protective agent is 0.01 parts by weight. This is because the main function of the modified protective agent is to react with the carbon in the protective slag through chromium to form a stable compound, thereby reducing the diffusion of carbon into the molten steel. When the addition amount is too low, the chromium concentration is not sufficient to effectively react with the carbon in the slag, resulting in incomplete reaction and inability to fully eliminate the carbon-rich layer, resulting in a significant reduction in the effect.

[0053] By comparing Example 2 and Comparative Example 2, it can be seen that the effect of eliminating the carbon-rich layer of the crystallizer is worse when malonic acid surface treatment is not used in the preparation of the modified protective agent. This is because malonic acid can enhance the dispersibility of metal particles in the protective slag, and metal particles that have not been treated with malonic acid are easy to agglomerate in the protective slag, resulting in uneven distribution in the slag, and cannot effectively contact with the carbon in the slag, thereby reducing the reaction efficiency.

[0054] By comparing Example 2 and Comparative Example 3, it can be seen that the effect of eliminating the carbon-rich layer of the crystallizer is worse when metallic chromium and metallic cadmium are directly added to the protective slag without mixing modification treatment and malonic acid surface treatment. This is because the melting point of metallic chromium is very high, while the melting point of metallic cadmium is relatively low. During the continuous casting process, the chromium with a high melting point cannot be completely melted, resulting in an inability to fully react with carbon, while the cadmium with a low melting point tends to melt prematurely, resulting in uneven distribution in the slag, thereby making the effect of eliminating the carbon-rich layer of the crystallizer poor.

[0055] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only preferred examples of the present invention, and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A protective slag for eliminating the carbon-rich layer of a crystallizer, characterized in that: The invention comprises the following components in parts by weight: 38-44 parts by weight of calcium oxide, 53-67 parts by weight of silicon dioxide, 8-13 parts by weight of calcium fluoride, 5-7 parts by weight of aluminum oxide, 3-9 parts by weight of magnesium oxide, 1-5 parts by weight of zirconium oxide, 4-6 parts by weight of flux and 1-3 parts by weight of modified protective agent; The modified protective agent is prepared by mixing metal chromium and metal cadmium in a mass ratio of 3:5-7, and then compounding with malonic acid after mixed modification. The specific preparation method of the modified protective agent is as follows: In an atmosphere of inert gas argon, a mixture of chromium and cadmium is heated to 1900-2000° C. using a high-frequency induction furnace, and heating and stirring are continued to ensure that all metals are completely melted and evenly mixed, and the molten alloy is poured into a preheated mold, and allowed to cool naturally to obtain a chromium-cadmium alloy, malonic acid is added to deionized water and stirred to form a solution, and the pH value is adjusted with a sodium hydroxide solution, and then the chromium-cadmium alloy is immersed in the above solution to ensure that the surface of the alloy is completely covered, and immersed in a constant temperature water bath. After the reaction is completed, the alloy sample is taken out from the solution, and is thoroughly washed with deionized water to remove unreacted malonic acid or other impurities, and washed with anhydrous ethanol, and dried naturally to obtain a modified protective agent.

2. The protective slag for eliminating the carbon-rich layer of the crystallizer according to claim 1, characterized in that: The mass fraction of the malonic acid is 12-18%.

3. The protective slag for eliminating the carbon-rich layer of the crystallizer according to claim 1, characterized in that: The molar concentration of the sodium hydroxide solution is 0.1-1 mol / L.

4. The protective slag for eliminating the carbon-rich layer of the crystallizer according to claim 1, characterized in that: The pH value is adjusted to 2-4.

5. The protective slag for eliminating the carbon-rich layer of the crystallizer according to claim 1, characterized in that: The temperature of the constant temperature water bath is set at 60-90° C., and the reaction time is 2-3 hours.

6. The protective slag for eliminating the carbon-rich layer of the crystallizer according to claim 1, characterized in that: The flux is one or more combinations of sodium oxide, potassium oxide and lithium oxide.

7. The protective slag for eliminating the carbon-rich layer of the crystallizer according to claim 1, characterized in that: The specific preparation method of the protective slag is as follows: Put calcium oxide, silicon dioxide, calcium fluoride, aluminum oxide, magnesium oxide and zirconium oxide into a mixer and mix them preliminarily for 30-40 minutes, then add the modified protective agent, and continue mixing for 10-20 minutes to make the protective agent evenly distributed in each component, put the mixed material into an oven, dry it at 100-120°C for 1-2 hours, put the dried material into a muffle furnace for calcination, and the calcined material is naturally cooled to room temperature. The cooled protective slag is sieved through a sieve to remove large particles to obtain a protective slag that eliminates the carbon-rich layer of the crystallizer.

8. The protective slag for eliminating the carbon-rich layer of the crystallizer according to claim 7, characterized in that: The muffle furnace calcination temperature is 800-1000° C., and the calcination time is 1-2 hours.

9. The protective slag for eliminating the carbon-rich layer of the crystallizer according to claim 7, characterized in that: The particle size of the protective slag is 0.2-1 mm.

Citation Information

Patent Citations

  • Apparatus and method for size reduction

    CN102844120A

  • Method for accurately positioning casting blank production process parameters to casting blank slices

    CN106735029A